The contrasting chemistry and cancer cell cytotoxicity of bipyridine and bipyridinediol ruthenium(II) arene complexes - Bugarcic, Tijana; Habtemariam, Abraha; Štěpánková, Jana; Heringová, Pavla; Kašpárková, Jana; Deeth, Robert J; Johnstone, Russell D; Prescimone, Alessandro; Parkin, Andrew; Parsons, Simon; Brabec, Viktor; Sadler, Peter J (Inorganic chemistry, 2008)
The synthesis and characterization of ruthenium(II) arene complexes [(eta(6)-arene)Ru(N,N)Cl](0/+), where N,N = 2,2'-bipyridine (bipy), 2,2'-bipyridine-3,3'-diol (bipy(OH)(2)) or deprotonated 2,2'-bipyridine-3,3'-diol (bipy(OH)O) as N,N-chelating ligand, arene = benzene (bz), indan (ind), biphenyl (bip), p-terphenyl (p-terp), tetrahydronaphthalene (thn), tetrahydroanthracene (tha) or dihydroanthracene (dha), are reported, including the X-ray crystal structures of [(eta(6)-tha)Ru(bipy)Cl][PF(6)] (1), [(eta(6)-tha)Ru(bipy(OH)O)Cl] (2) and [(eta(6)-ind)Ru(bipy(OH)(2))Cl][PF(6)] (8). Complexes 1 and 2 exibit CH (arene)/pi (bipy or bipy(OH)O) interactions. In the X-ray structure of protonated complex 8, the pyridine rings are twisted (by 17.31 degrees). In aqueous solution (pH = 2-10), only deprotonated (bipy(OH)O) forms are present. Hydrolysis of the complexes was relatively fast in aqueous solution (t(1/2) = 4-15 min, 310 K). When the arene is biphenyl, initial aquation of the complexes is followed by partial arene loss. Complexes with arene = tha, thn, dha, ind and p-terp, and deprotonated bipyridinediol (bipy(OH)O) as chelating ligands, exhibited significant cytotoxicity toward A2780 human ovarian and A549 human lung cancer cells. Complexes [(eta(6)-bip)Ru(bipy(OH)O)Cl] (7) and [(eta(6)-bz)Ru(bipy(OH)O)Cl] (5) exhibited moderate cytotoxicity toward A2780 cells, but were inactive toward A549 cells. These activity data can be contrasted with those of the parent bipyridine complex [(eta(6)-tha)Ru(bipy)Cl][PF(6)] (1) which is inactive toward both A2780 ovarian and A549 lung cell lines. DFT calculations suggested that hydroxylation and methylation of the bipy ligand have little effect on the charge on Ru. The active complex [(eta(6)-tha)Ru(bipy(OH)O)Cl] (2) binds strongly to 9-ethyl-guanine (9-EtG). The X-ray crystal structure of the adduct [(eta(6)-tha)Ru(bipy(OH)O)(9-EtG-N7)][PF(6)] shows intramolecular CH (arene)/pi (bipy(OH)O) interactions and DFT calculations suggested that these are more stable than arene/9-EtG pi-pi interactions. However [(eta(6)-ind)Ru(bipy(OH)(2))Cl][PF(6)] (8) and [(eta(6)-ind)Ru(bipy)Cl][PF(6)] (16) bind only weakly to DNA. DNA may therefore not be the major target for complexes studied here.
Keywords: Cell Survival; 2,2'-Dipyridyl; Models, Molecular; nádory plic; vodíková vazba; Hydrolysis; kationty; Lung Neoplasms; Humans; Tumor Cells, Cultured; hydrolýza; 2,2'-dipyridyl; Female; nádory vaječníků; Cations; krystalografie rentgenová; Ovarian Neoplasms; Crystallography, X-Ray; lidé; magnetická rezonanční spektroskopie; molekulární modely; nádorové buňky kultivované; hmotnostní spektrometrie s elektrosprejovou ionizací; ženské pohlaví; ruthenium; Hydrogen Bonding; nádorové buněčné linie; Spectrometry, Mass, Electrospray Ionization; Cell Line, Tumor; Magnetic Resonance Spectroscopy; Ruthenium; viabilita buněk